A “Dynasty” of Hellenists in twentieth-century Bucharest: Demosthene Russo, Ariadna Camariano-Cioran and Nestor Camariano - Rados, Leonidas (The Historical Review/La Revue Historique, 2012)
Romanian academic circles became more interested in the study of Greek-Romanian relations towards the end of the nineteenth century and in the early twentieth. Demosthene Russo, a young Greek immigrant to Romania, educated at Constantinople, Athens, Berlin and Leipzig, profited from this favourable trend; he managed to establish at the University of Bucharest, after 1915, a powerful centre for Byzantine and Neohellenic research and to impose his own critical school, based upon a rigorous method, in direct competition with the line directed by the most highly acknowledged Romanian historian, Nicolae Iorga, a researcher with many achievements and famous initiatives in South-East European studies. In the interwar period Russo took on the responsibility for the education of his nephew and niece, Nestor and Ariadna Camariano, to whom he transmitted his appetite for detailed research and critical methods in his field and whom he left to continue his work. The three have deeply marked the study of the history of Hellenism; they distinguished themselves, sometimes under unfavourable circumstances, by their valuable scientific production, opening new directions in the cultural history of South-East Europe.